Analisis Efektivitas Program Rehabilitasi Lingkungan dalam Pemulihan Ekosistem di Kawasan Pascatambang PT Bukit Asam Tbk, Tanjung Enim - Ikhsan Hilal Syafaat; Baruna Hafizd Xavire; Bintang Aji Tamadinta; Bayu Prastiyo; Reva Putri Sugianti; Laily Agustina Rahmawati (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to examine the implementation of post-mining environmental rehabilitation programs carried out by PT Bukit Asam Tbk in the Tanjung Enim mining area, South Sumatra. Coal mining activities have significant ecological impacts, especially on vegetation damage, soil erosion, and habitat degradation. In this context, rehabilitation efforts are a crucial step to restore the ecosystem and ensure environmental sustainability. The method used in this study is a qualitative literature study with a descriptive-analytical approach to official company documents, environmental reports, and relevant academic references. The results of the study indicate that PT Bukit Asam has implemented various rehabilitation strategies, including revegetation, wastewater management, and community empowerment through agroforestry programs. The success of this program is reflected in the increased vegetation cover, land stability, and biodiversity indicators in the reclamation area. However, challenges such as natural factors and limited supervision still need to be addressed. In conclusion, the rehabilitation practices carried out by this company can be used as a model for sustainable post-mining management in Indonesia. This study recommends the need for multi-sector collaboration and increased transparency and monitoring technology to support long-term effectiveness.